DJ stent and nephrostomy drainage outcomes for upper urinary tract obstruction and determinative factors for drainage selection - Guler, Yavuz (Annals of Medical Research, 2021)
Aim: To compare drainage outcomes from double J stent and percutaneous nephrostomy stent for upper urinary tract obstruction and to research factors determining the stent method to be used. Upper urinary tract obstruction may be caused by ureter and kidney stones internally or by local advanced-stage pelvic organ cancers externally and this may lead to sepsis or obstructive uropathy. It is necessary to drain the kidney immediately before definitive treatment of stone patients and prevent increased morbidity and mortality in cancer patients. Materials and Methods: A total of 213 patients with upper urinary tract obstruction and drainage using double J stent and percutaneous nephrostomy catheter were retrospectively assessed. Demographic, operative-postoperative data and predictive factors for stent selection were assessed.Results: The groups were different in terms of age and gender demographically, as well as disease duration before the procedure, comorbid diseases, causative factors, hydronephrosis degree and stone size (p 0.05). The groups were different in terms of operational data, operation time, auxiliary time, complications and definitive treatment for stones (p 0.05). Independent predictive factors for stent selection were stone size (Odds ratio:1.3), obstructive duration before the procedure (Odds ratio:1.1), causative factors (Odds ratio:38.1), and hydronephrosis degree (Odds ratio:10.5). Conclusion: For patients with long duration of obstruction and high degree of hydronephrosis, with obstruction caused by local advanced pelvic cancer and large ureter stones and with sepsis, percutaneous nephrostomy drainage should be chosen instead of double J stent drainage.